The viability of advanced welfare states in the international economy: Vulnerabilities and options - Fritz W. Scharpf (Max Planck Institute for the Study of Societies, 1999)
The paper represents a preliminary and partial analysis of the information collected in a comparative 12-country study of the adjustment of national employment and social-welfare policies to the increasing internationalization of product and capital markets. After the postwar decades, when national governments were still able to control their economic boundaries, the first international challenge came in the form of the oil-price crisis of 1973/74, which confronted industrial economies with the double threat of cost-push inflation and demand-gap unemployment. It could be met if countries were able to achieve a form of Keynesian concertation in which expansionary monetary and fiscal policies would defend employment while union wage restraint could be relied on to fight inflation. For this solution, corporatist industrial-relations institutions were a necessary but not a sufficient condition. Since the second oil-price crisis of 1979-80 was met by restrictive monetary and expansionary fiscal policies in the United States, the steep increase of real interest rates in the international capital markets forced other central banks to raise interest rates accordingly. As a consequence, employment-creating investments could only be maintained if the share of profits in the national product was significantly increased. Under the pressure of rapidly rising unemployment, unions in most countries were forced to accept this massive redistribution from labor to capital. In the 1990s, finally, the international integration of product and capital markets has been constraining private sector employment as well as the financial viability of the welfare state. But now institutional differences among different types of revenue systems, welfare states and employment systems - Scandinavian, Anglo-Saxon, and Continental - create important differences in vulnerability that can no longer be met by standardized responses. The paper concludes with an examination of the specific problems faced by, and the solutions available to, the different countries included in the study.
Keywords: 300